The Effectiveness of Waste Bank Management at Hidayah Waste Bank and Sejahtera Bersama Waste Bank in Lubuk Kilangan District - Drajat, Rian Rafiul; Junialdi, Rezi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effectiveness of waste bank management. This study was motivated by concerns about the environment which is increasingly filled with both organic and inorganic waste. Therefore, this study aims to analyze how waste banks are managed in Lubuk Kilangan District, Padang City. This study uses a qualitative approach. Then the data was collected through interviews, observations and documentation, then data analysis was carried out through three stages, namely data reduction, data presentation and drawing conclusions. The subjects of this study were the Hidayah Waste Bank and the Sejahtera Bersama Waste Bank in addition to the Lubuk Kilangan District community and Waste Bank Members. Based on the research results, it was found that the effectiveness of waste bank management at the Hidayah Waste Bank and Sejahtera Bersama Waste Bank which consistently run the waste bank program. The effectiveness indicator describes the range of consequences and impacts (outcomes) of the program output in achieving program objectives.